2020
DOI: 10.1186/s12909-020-02309-9
|View full text |Cite
|
Sign up to set email alerts
|

Resident satisfaction with the pediatric surgery training program

Abstract: Background The pediatric surgery residency program is new in Saudi Arabia. As with any new program, residents experience a degree of fear and anxiety about their future in the program. The aim of this study is to examine residents’ satisfaction with the program. Methods This study included an online survey examining residents’ satisfaction. It consisted of demographic, financial, personality, program-specific, and burnout assessment questions. All questions were multiple-choice items. Descriptive statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…The level of residents' satisfaction regarding the Saudi Board of Plastic Surgery program has been assessed using the following question: "How would you rate your overall satisfaction regarding your Saudi Board of Plastic Surgery residency program?" A five-point Likert scale was used to interpret the results; the options ranged from "not satisfied at all" (1) to "very satisfied" (5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The level of residents' satisfaction regarding the Saudi Board of Plastic Surgery program has been assessed using the following question: "How would you rate your overall satisfaction regarding your Saudi Board of Plastic Surgery residency program?" A five-point Likert scale was used to interpret the results; the options ranged from "not satisfied at all" (1) to "very satisfied" (5).…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional study, the authors structured a self-administered questionnaire in the light of available literature with similar objectives. [3][4][5][6]7 The questionnaire was revised by two experts in the field of plastic surgery to ensure the objectivity of the questions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, studies on neurosurgery residents showed higher overall satisfaction score compared to our report [ 15 , 16 ]. A study of pediatric surgery residents also found a high satisfaction rate [ 17 ]. On the other hand, satisfaction scores with regards to the training among urology residents are divergent across the literature, ranging from less than 30% to more than 80% [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%